A nod in the wrong direction : does non-verbal feedback affect eyewitness confidence in interviews? - Gurney, Daniel J.; Vekaria, Kishan N.; Howlett, Neil (Psychiatry, psychology, and law, 2014)
Influence of interviewers’ behaviour on eyewitnesses – positive feedback administered verbally – investigation of whether positive and negative non-verbal feedback could affect the confidence of witnesses attribute to their responses – witnesses presented with positive non-verbal feedback reported inflated confidence compared with negative non-verbal feedback regardless of accuracy – provides further insight into effects of interview behaviour in investigative interviews.